2013
DOI: 10.1108/wjstsd-08-2013-0035
|View full text |Cite
|
Sign up to set email alerts
|

Managing the environment, people and herds: sustainability of the Moroccan cedar forest

Abstract: Users who downloaded this article also downloaded: (2012),"4Es and 4 Poles model of sustainability: Redefining sustainability in the built environment", Structural Survey, Vol. 30 Iss 5 pp. 426-442 http://dx.Access to this document was granted through an Emerald subscription provided by emerald-srm:412925 [] For AuthorsIf you would like to write for this, or any other Emerald publication, then please use our Emerald for Authors service information about how to choose which publication to write for and submissi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 31 publications
(28 reference statements)
0
4
0
Order By: Relevance
“…Model simulations indicate an upward shift of the lower limit of their range in the Rif Mountains by about 200 m (Cheddadi et al, 2017). Recent decline in these mountains, however, is considered to have been induced by human activities, mainly cropping, cutting and overgrazing (Ajbilou et al, 2003; Benabid, 1985; Coudel et al, 2016; Grovel, 1996; Hamelin and Nwankwo, 2013; Moore et al, 1998; Rejdali, 2004). Disentangling the impact of each factor on landscape is not an easy task, although essential to take the appropriate managing measures to ensure the persistence of the modern populations (Allen et al, 2010; El-Baha et al, 2010; IRES, 2010; Vegas-Vilarrúbia et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Model simulations indicate an upward shift of the lower limit of their range in the Rif Mountains by about 200 m (Cheddadi et al, 2017). Recent decline in these mountains, however, is considered to have been induced by human activities, mainly cropping, cutting and overgrazing (Ajbilou et al, 2003; Benabid, 1985; Coudel et al, 2016; Grovel, 1996; Hamelin and Nwankwo, 2013; Moore et al, 1998; Rejdali, 2004). Disentangling the impact of each factor on landscape is not an easy task, although essential to take the appropriate managing measures to ensure the persistence of the modern populations (Allen et al, 2010; El-Baha et al, 2010; IRES, 2010; Vegas-Vilarrúbia et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…This objective is similar to the aim of Jorgensen and Knudsen (2006), that is to complete a study on the sustainable management of companies that explores opportunities for buyers to encourage providers to achieve sustainability. Finally, sustainability and corporate governance address the inadequacy of participatory management initiatives to improve the environment in regions characterized by poverty (Hamelin & Nwankwo, 2013). Gnan et al (2013) noted that there are organizations that fail to improve their corporate governance performance despite the implementation of OECD principles.…”
Section: Low Stakeholder Engagement Adversely Impacts Companies' Bott...mentioning
confidence: 99%
“…In addition, participatory management initiatives to improve the environment in regions with high levels of poverty are often inadequate (Hamelin & Nwankwo, 2013), specifically operational and tactical strategies that put more emphasis on ecology (Rossing, Jansma, De Ruijter, & Schans, 1997), while sustainability can improve product quality and encourage product consumption (Schacht, 2010). Finally, sustainability has a relationship link with corporate governance when managers consider sustainability as a means to increase the value of the organization (Klettner, Clarke, & Boersma 2014), which satisfies stakeholders (Gnan, Hinna, Monteduro, & Scarozza 2013) and reduces costs to increase profits (Lacy & Hayward, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…In the same vein, Driouech et al [7,8] anticipated extreme climate changes in the MENA region. Hamelin and Nwankwo [9,10] showed that reduced precipitation and increased temperature in Morocco are the main drivers of the decline of the cedar forest. On a national level, Egypt, like many other countries, is significantly affected by climate change, experiencing increased temperatures, changes in rainfall patterns leading to more extreme weather events, rising sea levels threatening its crucial Nile Delta, and land degradation that reduces its agricultural capacity [11][12][13].…”
Section: Introductionmentioning
confidence: 99%